Transformation of Midwives' Independent Practice in The Era of Law No. 17 of 2023: Between Regulations, Challenges and Opportunities - Katmi, Katmi; Katno, Katno; Prayuti, Yuyut (Dinasti Research, 2025)
The enactment of Law no. 17 of 2023 concerning Health brings significant changes to the independent practice of midwives, especially in aspects of regulation, licensing and authority. This regulation aims to improve the quality of health services, but also presents challenges for midwives in carrying out their practice. This research aims to analyze the impact of implementing Law no. 17 of 2023 regarding the independent practice of midwives, as well as identifying challenges and opportunities that arise as a result of changes to these regulations. This research uses a qualitative approach with document analysis methods, which involves a study of Law no. 17 of 2023, as well as scientific journal articles, WHO reports and relevant previous research. The research results show that this policy causes changes in the risk-based licensing system, increasing the authority of midwives, but also creates challenges in terms of regulatory adaptation, licensing costs, and the need for additional training. On the other hand, this regulation provides opportunities to simplify licensing procedures for low-risk services, stronger legal protection, and integration of health technology. Implementation of Law no. 17 of 2023 requires a good adaptation strategy so that midwives can adapt their practices to new regulations, while also taking advantage of opportunities to improve the professionalism and quality of maternal and child health services in Indonesia.